Pelecehan Seksual Terhadap Anak-Anak: Implikasi Hukum Pidana dan Perlindungan Anak - Muthi’ah Lathifah; Jojor Mindo Manullang; Reh Bungana; Maulana Ibrahim (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
It is important to understand the true definition of sexual abuse of children. Child sexual abuse refers to behavior in which adults or older individuals take advantage of children to fulfill their sexual needs. Actions carried out on children can have long-lasting traumatic impacts that can disturb them and even the people around them. Sexual violence against children is so common that it has become a global problem today. In particular, Indonesia has its own law protecting children who experience sexual abuse. The purpose of this article is to explain the implications of criminal law and the challenges faced in dealing with sexual abuse of children. As well as explaining the impact of abuse on children. To help provide an explanation of the research, the method used in this research is literature study and analytical methods